Effectiveness of Educational Videos about Stunting Via Tiktok and Instagram on Adolescent Knowledge - Rini Ernawati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Stunting is a nutritional disorder in toddlers, marked by height below the average for their age due to chronic malnutrition. This condition results in growth failure, impaired cognitive function, and a higher risk of degenerative diseases like diabetes, hypertension, and stroke. Teenagers, as future parents, have an essential role in breaking the cycle of stunting. Currently, teenagers are active social media users, particularly on TikTok and Instagram, which can serve as educational platforms. This study aims to assess the impact of educational videos on stunting through TikTok and Instagram on grade 11 students' knowledge at SMA Negeri 4 Samarinda. The research design is quasi-experimental with a pretest-posttest control group. Purposive sampling selected 80 students from a population of 235. Data were collected through pre-test and post-test questionnaires. Univariate and bivariate data analysis included the Wilcoxon test and paired t-test. Results showed significant effects on knowledge, with p-values of 0.001 for TikTok (Wilcoxon test) and 0.000 for Instagram (paired t-test). This study highlights the potential of social media as a tool for health promotion, especially in educating adolescents on stunting prevention.